LITERATURE REVIEW: PENGARUH SARI KACANG HIJAU DAN MADU SERTA TABLET FE TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL - Alamanda Putri Karundra; Ayuni; Farsya Talahah; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Anemia in pregnancy is a condition where the hemoglobin level is below 11 g/dL. This condition can impact fetal growth and development and increase the risk of bleeding in the mother. One of the main causes of anemia is iron deficiency, which can be minimized by consuming foods high in iron, including mung bean juice. This study aims to analyze the effectiveness of administering mung bean juice and honey and iron tablets in increasing hemoglobin levels in pregnant women. The research method used a literature review with data sources from Google Scholar, consisting of three journals selected based on publication criteria from 2021–2025 and relevance to keywords. The results of the review indicate that regular consumption of mung bean juice with added honey and iron tablets significantly increases hemoglobin levels in pregnant women. Thus, mung bean juice with added honey and iron tablets has the potential to be a simple nutritional intervention that is beneficial in preventing anemia in pregnancy.